2000
DOI: 10.1148/radiology.215.3.r00jn01863
|View full text |Cite
|
Sign up to set email alerts
|

Irreversibly Damaged Myocardium at MR Imaging with a Necrotic Tissue-Specific Contrast Agent in a Cat Model

Abstract: MR images enhanced with bis-gadolinium mesoporphyrins provide accurate sizing of irreversibly damaged myocardium with a strong and persistent signal enhancement in the reperfused myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 19 publications
(19 reference statements)
2
38
1
Order By: Relevance
“…Choi et al 19 claimed that mesoporphyrin produced maximum enhancement 1 to 3 hours after intravenous injection in cats with reperfused myocardial infarction. It is certainly true that greater myocardial enhancement by mesoporphyrin occurs early after the agent is administered.…”
Section: Characterization Of Ischemically Injured Myocardiummentioning
confidence: 99%
See 1 more Smart Citation
“…Choi et al 19 claimed that mesoporphyrin produced maximum enhancement 1 to 3 hours after intravenous injection in cats with reperfused myocardial infarction. It is certainly true that greater myocardial enhancement by mesoporphyrin occurs early after the agent is administered.…”
Section: Characterization Of Ischemically Injured Myocardiummentioning
confidence: 99%
“…Mesoporphyrin provides accurate sizing of occlusive and reperfused infarctions. [17][18][19] The purpose of this study was (1) to characterize the peri-infarction zone in moderately injured myocardium by use of the combination of Gd-DTPA and mesoporphyrin MR contrast media and (2) to determine the function (wall thickening) of regions enhanced by Gd-DTPA and mesoporphyrin. The major hypothesis of this study is that the difference in the areas demarcated by the 2 agents is the salvageable border zone with reduced but residual contractile function.…”
mentioning
confidence: 99%
“…However, it is a post-mortem technique and not clinically applicable. Studies with both intravenous and intracoronary NACA injections have revealed that what is specifically enhanced on cardiac MRI corresponds exactly to what TTC dye does not stain on the excised heart, resulting in the same accuracy for MI delineation (Ni et al 1994(Ni et al , 2001bMarchal et al 1996;Herijgers et al 1997;Ni 1998;Lim et al 1999;Pislaru et al 1999;Saeed et al 1999;Stillman et al 1999;Wendland et al 1999;Choi et al 2000;Marchal and Ni 2000;Jeong et al 2001;Jin et al 2007) (Fig. 1).…”
Section: 4mentioning
confidence: 93%
“…The local concentration of Gd is frequently over tens of times higher in infarcted compared with normal myocardium. Finally, the potent effects of Gadophrin-2 for labeling spontaneous and therapeutic necroses, including MI and lesions of radiofrequency ablation (RFA) on MRI, have been widely recognized a few years later, after multi-institutional reproducibility studies (Lim and Choi 1999;Saeed et al 1999;Stillman et al 1999;Wendland et al 1999;Choi et al 2000;Jeong et al 2001;Saeed et al 2001;Barkhausen et al 2002;Ni et al 2005c;Ni et al 2006a).…”
Section: 4mentioning
confidence: 99%
See 1 more Smart Citation